1989
DOI: 10.1186/1297-9686-21-4-527
|View full text |Cite
|
Sign up to set email alerts
|

Sélection sur la vitesse de croissance post-sevrage chez le lapin

Abstract: On a effectué une expérience de sélection massale sur la vitesse de croissance entre le sevrage (30 j) et 77 j dans une souche de lapin. La souche sélectionnée se composait de 12 mâles et 60 femelles pendant les 4 premières générations puis de 8 mâles et 40 femelles pendant les 4 suivantes. La souche témoin se composait aussi de 8 mâles et de 40 femelles. On a réalisé une intensité de sélection de 0,95. La vitesse de croissance postsevrage est améliorée de 6,9 g pour 8 générations, soit un progrès de 0,83 g pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
2
2

Year Published

1991
1991
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 10 publications
3
39
2
2
Order By: Relevance
“…Similarly, the estimated heritability value for ADG between 4 and 9 wk was very similar to the value reported by Piles et al [28], but was slightly higher than that reported in rabbits selected on 70-d mass weight (0.17, [18]) or for 4 to 10 wk ADG (0.23, [34]). The high positive genetic correlation between 63-d body weight and 4 to 9 wk ADG, was close to that reported between 70-d body weight and 3-4 to 10 wk ADG (r g = 0.91 to 0.98, [18,40]).…”
Section: Genetic Parameters For Growth Performance and Qualitative Trsupporting
confidence: 86%
See 3 more Smart Citations
“…Similarly, the estimated heritability value for ADG between 4 and 9 wk was very similar to the value reported by Piles et al [28], but was slightly higher than that reported in rabbits selected on 70-d mass weight (0.17, [18]) or for 4 to 10 wk ADG (0.23, [34]). The high positive genetic correlation between 63-d body weight and 4 to 9 wk ADG, was close to that reported between 70-d body weight and 3-4 to 10 wk ADG (r g = 0.91 to 0.98, [18,40]).…”
Section: Genetic Parameters For Growth Performance and Qualitative Trsupporting
confidence: 86%
“…Successful selection in rabbits was previously shown for ADG [4,22,35] and body weight at market age [18,34]. However, a higher genetic progress for body weights and ADG was obtained in the present work, mainly because of the efficiency of selection on BLUP breeding values in comparison with selection on phenotypic values.…”
Section: Symmetrical and Asymmetrical Responses For Selection On Bodymentioning
confidence: 58%
See 2 more Smart Citations
“…Then, when the relationship matrix is complete and the animal model is used, the trend in estimated breeding value may give a reasonable approximation to the genetic response for traits of moderate to high heritability. This has been checked by Mrode et al (1989a, b) (Mgheni and Christensen, 1985;Rochambeau et al, 1989) (Camacho, 1989) and there is also evidence that the genetic response in WG is associated with correlated response in SW (Estany et al, 1988b;Camacho, 1989;Rochambeau et al 1989). If that is the case, cross-fostering to equalize litter size would be worthwhile to reduce any maternal effect on SW.…”
Section: Discussionmentioning
confidence: 90%